Extrahepatic Surgery in Cirrhosis Significantly Increases Portal Pressure in Preclinical Animal Models - Chang, Johannes; Meinke, Jonathan; Geck, Moritz; Hebest, Marc; Böhling, Nina; Dolscheid-Pommerich, Ramona; Stoffel-Wagner, Birgit; Kristiansen, Glen; Overhaus, Marcus; Peyman, Leon O.; Klein, Sabine; Uschner, Frank E.; et al. (Frontiers in Physiology, 2021)
Background Liver cirrhosis is a relevant comorbidity with increasing prevalence. Postoperative decompensation and development of complications in patients with cirrhosis remains a frequent clinical problem. Surgery has been discussed as a precipitating event for decompensation and complications of cirrhosis, but the underlying pathomechanisms are still obscure. The aim of this study was to analyze the role of abdominal extrahepatic surgery in cirrhosis on portal pressure and fibrosis in a preclinical model. Methods Compensated liver cirrhosis was induced using tetrachlormethane (CCL4) inhalation and bile-duct ligation (BDL) models in rats, non-cirrhotic portal hypertension by partial portal vein ligation (PPVL). Intestinal manipulation (IM) as a model of extrahepatic abdominal surgery was performed. 2 and 7 days after IM, portal pressure was measured in-vivo. Hydroxyproline measurements, Sirius Red staining and qPCR measurements of the liver were performed for evaluation of fibrosis development and hepatic inflammation. Laboratory parameters of liver function in serum were analyzed. Results Portal pressure was significantly elevated 2 and 7 days after IM in both models of cirrhosis. In the non-cirrhotic model the trend was the same, while not statistically significant. In both cirrhotic models, IM shows strong effects of decompensation, with significant weight loss, elevation of liver enzymes and hypoalbuminemia. 7 days after IM in the BDL group, Sirius red staining and hydroxyproline levels showed significant progression of fibrosis and significantly elevated mRNA levels of hepatic inflammation compared to the respective control group. A progression of fibrosis was not observed in the CCL4 model. Conclusion In animal models of cirrhosis with continuous liver injury (BDL), IM increases portal pressure and development of fibrosis . Perioperative portal pressure and hence inflammation processes may be therapeutic targets to prevent postoperative decompensation in cirrhosis.